2020
DOI: 10.1186/s12870-020-2272-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals insight into molecular hydrogen-induced cadmium tolerance in alfalfa: the prominent role of sulfur and (homo)glutathione metabolism

Abstract: Background: Hydrogen gas (H 2) is hypothesised to play a role in plants that are coping with stresses by regulating signal transduction and gene expression. Although the beneficial role of H 2 in plant tolerance to cadmium (Cd) has been investigated previously, the corresponding mechanism has not been elucidated. In this report, the transcriptomes of alfalfa seedling roots under Cd and/or hydrogen-rich water (HRW) treatment were first analysed. Then, the sulfur metabolism pathways were focused on and further i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 66 publications
(132 reference statements)
1
19
0
Order By: Relevance
“…Similarly, analysis of the EDX spectrum in potato exposed to different Cd concentrations indicated that the highest amount of Cd was stored in the mesophilic tissue of leaves by binding to S-rich compounds [230]. A study on alfalfa under Cd stress conditions indicated that Cd tolerance in seedling roots was enhanced by increasing levels of the expression of genes associated with sulfur metabolism, especially genes implicated in GSH and PCs biosynthesis, also ABC transporters [231]. Due to the low pH of vacuoles, Cd-PCs complexes disassociate, and Cd can be stabilized in vacuoles by binding to ligands, including organic acids and probably amino acids [232].…”
Section: Phytochelatins and Metallothionein For Cadmium Phytoremediationmentioning
confidence: 99%
“…Similarly, analysis of the EDX spectrum in potato exposed to different Cd concentrations indicated that the highest amount of Cd was stored in the mesophilic tissue of leaves by binding to S-rich compounds [230]. A study on alfalfa under Cd stress conditions indicated that Cd tolerance in seedling roots was enhanced by increasing levels of the expression of genes associated with sulfur metabolism, especially genes implicated in GSH and PCs biosynthesis, also ABC transporters [231]. Due to the low pH of vacuoles, Cd-PCs complexes disassociate, and Cd can be stabilized in vacuoles by binding to ligands, including organic acids and probably amino acids [232].…”
Section: Phytochelatins and Metallothionein For Cadmium Phytoremediationmentioning
confidence: 99%
“…Interestingly, the production of H 2 has been observed in plants under the normal or stressed conditions [ 10 , 11 , 12 ], although its detailed synthetic pathway (s) are not fully elucidated. Further studies have revealed that H 2 played an important role in defense responses of plants to abiotic stresses [ 13 , 14 , 15 ], plant growth [ 16 ], and secondary metabolism [ 17 ]. H 2 was beneficial to postharvest preservation of fruits (kiwifruit [ 18 , 19 ] and tomato [ 20 ]) and cut flowers (rose [ 21 ], lily [ 22 ], and Lisianthus [ 23 ]).…”
Section: Introductionmentioning
confidence: 99%
“…H 2 fits into this suite of reactive signalling molecules and was shown to increase the fitness of plants [24]. Suitable examples of recent papers on H 2 effects on plants include mitigation of salinity effects in barley [25] and Arabidopsis [26], and increased tolerance to cadmium in alfalfa [27]. However, exactly how H 2 interacts and has an effect is unclear.…”
Section: Introductionmentioning
confidence: 99%